Effect of Trenches with Organic Matter and KCl Fertilizer on Growth and Yield of Upland Rice in Eucalyptus Agroforestry System - Ratnasari, Putri; Tohari, Tohari; Hanudin, Eko; Suryanto, Priyono (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2020)
Rice production can be improved through extensification using sub-optimal lands. One type of land that can be used for extensification of rice production in D.I. Yogyakarta is eucalyptus agroforestry system in Playen, Gunung Kidul. Besides expanding the land use, it can also increase farmers’ income and ecological functions. However, this system has limiting factors such as the limited availability of water, which only relies on rain. Thus, proper water management and fertilization are necessary to fulfill water and nutrient requirements for rice growth. This study aimed to determine the effects of the application of trenches with organic matter and the doses of KCl on the growth and yield of upland rice (Situ Patenggang) in eucalyptus agroforestry systems. The study was conducted at the Menggoran Forest Management Resort, Bleberan, Playen, Gunung Kidul in March-August 2018. The study was arranged in a split-plot design with three blocks as replications. The first factor was the application of trenches with organic matter, while the second factor was KCl fertilizer at. various doses. The data obtained were analyzed using analysis of variance (ANOVA) at the level of 5%. The optimal dose of KCl fertilizer was determined by regression. The results showed that both factors had a positive effect on soil moisture content, growth, physiology, and yields of upland rice. The treatments significantly increased the availability of water in the soil, thereby supporting the growth and yield of upland rice.